Great power comes at a high (locomotor) cost: the role of muscle fascicle length in the power versus economy performance trade-off - Cooper, A. N.; McDermott, W. J.; Martin, J. C.; Dulaney, S.O.; Carrier, D. R. (Journal of Experimental Biology, 2021)
Muscle design constraints preclude simultaneous specialization of the vertebrate locomotor system for explosive and economical force generation. The resulting performance trade-off between power and economy has been attributed primarily to individual differences in muscle fiber type composition. While certainly crucial for performance specialization, fiber type likely interacts with muscle architectural parameters, such as fascicle length, to produce this trade-off. Longer fascicles composed of more serial sarcomeres can achieve faster shortening velocities, allowing for greater power production. Long fascicles likely reduce economy, however, because more energy-consuming contractile units are activated for a given force production. We hypothesized that longer fascicles are associated with both increased power production and locomotor cost. In 11 power-trained and 13 endurance-trained recreational athletes, we measured (1) muscle fascicle length via ultrasound in the gastrocnemius lateralis, gastrocnemius medialis and vastus lateralis, (2) maximal power during cycling and countermovement jumps, and (3) running cost of transport. We estimated muscle fiber type non-invasively based on the pedaling rate at which maximal cycling power occurred. As predicted, longer gastrocnemius muscle fascicles were correlated with greater lower-body power production and cost of transport. Multiple regression analyses revealed that variability in maximal power was explained by fiber type (46% for cycling, 24% for jumping) and average fascicle length (20% for cycling, 13% for jumping), while average fascicle length accounted for 15% of the variation in cost of transport. These results suggest that, at least for certain muscles, fascicle length plays an important role in the power versus economy performance trade-off.